Physical activity levels and junk food intake among female undergraduate students in Mandya: a cross sectional study - K., Monisha; S., Poornima; M., Vinay (International Journal Of Community Medicine And Public Health, 2024)
Background: Physical activity (PA) is defined as any bodily movement produced by skeletal muscles that requires energy expenditure. It has been proven that regular physical activity helps control and prevent noncommunicable diseases like diabetes, heart disease, stroke, and several types of cancer. This study aimed to describe the levels of physical activity among female undergraduate students in Mandya and to assess their knowledge, attitude and practice regarding junk food habits. Methods: This cross-sectional study was done in Government women’s degree college, Mandya district, South Karnataka between November 2023 to December 2023 among female undergraduate students in the institute. Global physical activity questionnaire (GPAQ) has been used to describe their physical activity levels. Descriptive statistics like frequency, proportion, mean and standard deviation has been used. Results: The study was conducted among 170 students. Based on the MET values it is found that majority of them had moderate level of PA 81 (47.6%), while 39(22.9%) had high levels and 50 (29.4%) had low PA levels. Of 170 participants, 43 (25%) had junk food intake once a week, 46 (27%) had twice a week, 81 (48%) had thrice or more per week. The association between PA level and junk food was found to be statistically significant (p<0.05). Conclusions: The findings of this study help us in understanding the importance of adopting a healthy lifestyle, including a balanced diet and regular physical activity practice.